Summer nights - Mallery, Susan (Don Mills, Ont. : HQN, 2012)
Horse whisperer Shane Stryker, who is looking for a sensible woman who will be content with the quiet life of a rancher's wife, sets his sights on small-town librarian Annabelle Weiss, who has a wild side that tests his resolve.
Keywords: Ranchers -- Fiction; Women librarians -- Fiction; Love stories